Functional Assessment and Intervention by Nursing Assistants in Hospice and Palliative Care Inpatient Care Settings: A Quality Improvement Pilot Study. (March 2016) - Mueller, Karen; Hamilton, Gillian; Rodden, Betheny; DeHeer, Hendrick D.
This study assessed the impact of a nursing assistant-led functional intervention in an urban hospice. Thirty-three patients participated. A physical therapist trained 4 nursing assistants to assess 4 basic functional activities at admission and discharge and to provide daily activity training to intervention group participants. Control group participants were assessed at admission and discharge and received the usual standard of care. Both groups improved. The intervention group participants demonstrated significant improvement in the Timed up and Go test as well as their self-reported ability to achieve goals on the Patient-Specific Functional Scale. Control group participants made significant improvements in the ability to move from supine to sit in bed. These findings suggest that nursing assistants can provide activity-based assessment and intervention leading to improved function among patients in hospice.